2013
DOI: 10.1128/ec.00287-12
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DNA Release Acts as an Antifungal Resistance Mechanism in Mature Aspergillus fumigatus Biofilms

Abstract: dAspergillus fumigatus has been shown to form biofilms that are associated with adaptive antifungal resistance mechanisms. These include multidrug efflux pumps, heat shock proteins, and extracellular matrix (ECM). ECM is a key structural and protective component of microbial biofilms and in bacteria has been shown to contain extracellular DNA (eDNA). We therefore hypothesized that A. fumigatus biofilms also possess eDNA as part of the ECM, conferring a functional role. Fluorescence microscopy and quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
143
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(160 citation statements)
references
References 58 publications
(103 reference statements)
13
143
1
3
Order By: Relevance
“…The production of eDNA has been associated to hyphal growth [58]. Nevertheless, the present study demonstrated that even in the absence of hyphae (e.g.…”
Section: Discussioncontrasting
confidence: 56%
“…The production of eDNA has been associated to hyphal growth [58]. Nevertheless, the present study demonstrated that even in the absence of hyphae (e.g.…”
Section: Discussioncontrasting
confidence: 56%
“…The results of these studies add to an emerging body of evidence that fungal biofilms share structural (32)(33)(34)(35) and functional (26,36,37) similarity with those formed by pathogenic bacteria. The finding that glycoside hydrolases can display activity against the exopolysaccharides and biofilms of both fungi and bacteria provides evidence that these similarities could potentially be exploited for the development of therapeutics active against both organisms.…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, hydrolysis of cationic Pel exopolysaccharide by PelA h enhances the activity of the polycationic antibacterial colistin (22). Interestingly, degradation of biofilm-associated extracellular DNA (eDNA) has been reported to enhance A. fumigatus susceptibility to caspofungin and amphotericin B, although the effects on posaconazole and voriconazole susceptibility were not reported in the study (26). Recent work has suggested that Pel anchors eDNA within P. aeruginosa biofilms through charge-charge interactions (17).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therapy with recombinant DNase reduces C. albicans biofilm biomass and enhances the activity of amphotericin B, but not fluconazole, in vitro (76,77). Similarly, recombinant DNase was found to disrupt A. fumigatus biofilms and to enhance the activity of several antifungal agents in vitro (78). No studies in animal models evaluating the effects of DNase on antifungal susceptibility have been reported to date.…”
Section: Therapeutics Targeting Fungal Biofilmsmentioning
confidence: 99%